228k views
0 votes
Helpppppppppppppppppppppppppppppp

Helpppppppppppppppppppppppppppppp-example-1
User Rachita
by
5.6k points

2 Answers

4 votes
root (-108) -raiz (-3)
First we rewrite the expressions:
root (-36 * 3) -raiz (-3)
6 * root (-3) -raiz (-3)
5 * root (-3)
5 * root (3) * root (-1)
By definition:
i = root (-1)
Substituting:
5 * root (3) * i
Answer:
5 * root (3) * i
option 1
User Oddthinking
by
5.8k points
6 votes
The answer is A. \sqrt(-108)=sqrt(-1*108)=sqrt(-1)*sqrt(108)=i*\sqrt(36*3)=i*\sqrt(36)*\sqrt(3)=6i*\sqrt(3). \sqrt(-3)=\sqrt(-1*3)=\sqrt(-1)*\sqrt(3)=i*\sqrt(3). \sqrt(-108)-\sqrt(-3)=6i*\sqrt(3)-i*\sqrt(3)=5i*\sqrt(3).
User Snorbuckle
by
5.4k points